Rivaroxaban versus vitamin K antagonist treatment on the progression of coronary calcification: the IRIVASC-trial. - Stöhr, Robert; Reinartz, Sebastian; Dirrichs, Timm; Witte, Klaus; Schuh, Alexander; Brandenburg, Vincent (Scientific Reports, 2024)
Vitamin K antagonists (VKA) remain the only option of anticoagulation for people with mechanical valve replacement and due to their wider availability and lower acquisition costs, VKA's remain widely used in low- and middle-income countries. It has been suggested that prolonged use of VKAs can increase the development of vascular and valvular calcification, though this effect has not been examined in larger randomized prospective trials. This investigator-initiated multicenter, prospective, randomized, open-label interventional trial randomized patients with baseline coronary or valvular calcification and an indication for prolonged oral anticoagulation therapy to Marcumar or Rivaroxaban. Patients were followed-up through repeat coronary computed tomographies to measure the progression of coronary and valvular calcification for up to 24 months. 192 patients were randomized between 2013 and 2018 to receive either Rivaroxaban or Marcumar and followed for up to 24 months. Coronary calcification significantly increased over time although there was no significant difference in progression between the groups after 12 and 24 months as measured by the Agatston score [360.7 (90.2; 1075.3) vs 380.4 (136.4; 1546.9) p = 0.69], the volume score [295.8 (93.0; 995.3) vs 335.5 (128.7; 1316.9) p = 0.95] and the mass score [58.5 (15.9; 172.0) vs 71.1 (24.8; 257.3) p = 0.5]. Dephosphorylated, uncarboxylated matrix Gla Protein (Dp-ucMGP) significantly decreased in the VKA group [Δ dp-uc MGP - 95.2 (- 554.1; 156.0) vs 231.3 (- 59.7; 388.1) p < 0.001]. There does not appear to be a relevant effect of vitamin K inhibition by the vitamin K antagonist marcumar upon coronary calcification.
EVALuna2:570113